Answer:
(-2,12)
Step-by-step explanation:
The other endpoint would have to be (-5,2), going off the definition of a midpoint. Since 3 is for units to the right of -1, that would mean that the other end point would have to be 4 units to the left, which is -5.
Let's check your answer. To do this, you would simply plug your answer into the equation and see if it works.
5(y - 3) - 2 (3 - 2y) = 6
5(3 - 3) - 2(3 - 2 × 3) = 6
The equation works!
Y = 3
Great work!
D. Will be the correct answer
Answer:
y + 5 = -2
Step-by-step explanation:
That would be y + 5 = -2